Manajemen Krisis Ekonomi dalam Pemikiran Umar Bin Khattab - Mohamad Ainun Najib; Muhamad Fakhrudin (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2022)
The economic crisis is not only happening now but has been going on for a longtime. Among them during Umar bin Khattab. In this study, the method used isdescriptive qualitative, by using content analysis techniques and library researchtechniques. Among the strategies carried out by Caliph Umar bin Khattab was themanagement of Baitul Mal by maximizing Zakat, Ushr and other opinions,conducting a special distribution pattern related to the distribution of food fairlyand equitably, and the personal leadership factor of Umar bin Khattab.